Sinergisitas Hukum Peran Dinas Syariat Islam Dan Kepolisian Kota Langsa Dalam Pemberantasan Maisir - Muklis Muklis; Abdillah Abi Imanu (Iuris Studia: Jurnal Kajian Hukum, 2021)
Gambling or Maisir is a criminal act, namely betting a sum of money, having a fate with every game that is lucky for the players, including all other bets where this crime is found in all circles and the community, the main problem discussed is regarding the sanction procedure. against the perpetrators of maisir, especially in Langsa City, which uses the Qanun on the Jinayat Law and the Criminal Law which go hand in hand in imposing sanctions on the perpetrators of maisir. This study uses a qualitative research method with an empirical approach by collecting data from the field through the Islamic Shari'a Service and the Police with interviews and observations as the premier data source. The results obtained show that gambling crimes are regulated in Aceh Qanun No. 6 of 2014 concerning the Jinayat Law regarding maisir which has the aim of preventing and overcoming maisir crime and the Nanggroe Aceh Province Qanun No. 13 of 2013 concerning Maisir (gambling) is in accordance with the ta'zir hukuman punishment in Islamic Criminal Law